The Development of Applications using Augmented Reality Technology as the Teaching Media of Special Mirror Lights - Rosynanda Nur Fauziah; Dwi Sulisworo (Universitas Muhammadiyah Makassar, 2021)
This research was conducted due to the low interest of researchers to develop applications using smartphone-based Augmented Reality technology. The objective of this study was to produce a teaching media based on smartphone applications using augmented reality technology. The research method used was research and development with a 4D (Four-D) development model, which consisted of 4 stages, namely Define, Design, Develop, and Disseminate, which aimed to produce products with experts validity, namely media and material experts and also students’ responses. The results of assessment in the teaching media development conducted by the media experts was 4.273 (Good), while the assessment value from the material experts was 4.291 (Good). The average value of students' responses was 4.083, and it can also classified as Good. It means that the applications can be used as teaching media in the classroom to boost innovation for efficient and interactive teaching. Therefore, it can be concluded that the applications are suitable for use and apply in learning activities.